Pai Teacher's Strategy to Develop Students' Self Control at Ma Al-Fakhriyah 2 Baturaja - Azwar Aripin; H. Reza Fahlepi (Journal of Educational Analytics, 2023)
The purpose of this research is to provide education to students in order to reach maturity optimally. Descriptive qualitative research is the type of this research. The data sources are a number of students of MA Al-Fakhriyah 2 Baturaja, the head of the madrasah and his deputy, as well as an Islamic Religious Education teacher. Three data collection methods were used: documentation, interview, and observation. Qualitative analysis technique was used for data analysis. The results of this study show that: First, students' self-control in the cognitive control aspect is encouraging students to read books, teaching them to get used to reading the Qur'an and directing students to literature that records the events of the Islamic glory period. Second, students' self-control in the aspect of decisional control, specifically encouraging students to actively ask questions and provide explanations for any material they have not understood during the question and answer session at the end of the lesson. Third, students' self-control in the aspect of behavior is to provide exemplary, especially the attitude of modeling good behavior to students so that students can be used as role models in behaving well; Students are also expected to receive punishment or sanctions intended to prevent them from deviant behavior in the future.